COVID-19 aus Sicht der Intensivmedizin - Stecher, Stephanie-Susanne; Stemmler, Hans Joachim; Eichenauer, Dennis; Kochanek, Matthias; Shimabukuro-Vornhagen, Alexander; von Bergwelt-Baildon, Michael; Böll, Boris (DMW - Deutsche Medizinische Wochenschrift, 2020)
Approx. 93 % of COVID-19 infections are mild, and not all severely ill patients are transferred to the intensive care unit. But the Corona crisis implies high demands on intensive care medicine. Many treatment modalities of COVID patients are “best practice”, but some aspects remain unclear at present. This article deals with diagnostics, monitoring and therapy with COVID-19 patients in intensive care units and with a suitable hygiene concepts.A hygiene concept is obligatory and must ensure – in addition to general measures – the training of employees and the hygienic discharge of material. Ideally, a cohort isolation is implemented.Monitoring of patients with COVID-19 is not different from other intensive care patients and should be adapted to the clinical situation of the individual patient. In laboratory analysis the typical abnormality of COVID-19 patients should be taken into account. In case of increasing inflammatory parameters, fungal infections should be tested.Due to the formation of aerosols, disconnection of the respiratory system must be avoided in invasive ventilation. If a disconnection from the respirator is necessary, the tube should be disconnected. After extubation, an intermittent NIV treatment for atelectase prophylaxis can be performed.
Keywords: Intensivmedizin; COVID-19; ARDS, SOP